2020
DOI: 10.20429/ijsotl.2020.140104
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspectives in the Core: Student Attitudes and Instructor Performance

Abstract: Global learning and global citizenship education (GCE) continue to be integrated as co-curricular and curricular components in US higher education. Many institutions have linked their mission and values statements to global learning. However, their efforts fail to reflect a single shared understanding or philosophy of global learning or GCE. While scholars continue to discuss and debate the substance of these frameworks, few studies have analyzed perspectives of curricular global learning and GCE requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…However, many other students shared that selection was based upon non-curricular issues such as finding a class that fit their schedule. These findings are consistent with the previous quantitative assessment of the GC2Y program which revealed that both the day/time of the course offering, and title of the course were most likely to influence students' course selection (Butler & Reinke, 2020). Like faculty, students believe the GC2Y program provides a strong connection to the liberal arts mission of the university.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, many other students shared that selection was based upon non-curricular issues such as finding a class that fit their schedule. These findings are consistent with the previous quantitative assessment of the GC2Y program which revealed that both the day/time of the course offering, and title of the course were most likely to influence students' course selection (Butler & Reinke, 2020). Like faculty, students believe the GC2Y program provides a strong connection to the liberal arts mission of the university.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, although they did not provide clear definitions of global learning during focus groups, they reported that their courses strengthened their knowledge of diversity and prepared them as a more knowledgeable citizen. The previous assessment of the GC2Y program has also demonstrated that undergraduate students have positive attitudes towards global learning (Butler & Reinke, 2020). For example, the majority of students believed global issues courses helped them understand their place in the world, that they help them understand social issues, and that they are interested in becoming a better global citizen (Butler & Reinke, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations